Reveal it or conceal it: On the value of second opinions in a low-entry-barriers credence goods market - Parampreet Christopher Bindra; Rudolf Kerschbamer; Daniel Neururer; Matthias Sutter (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
Credence goods markets with their asymmetric information between buyers and sellers are prone to large inefficiencies. In theory, poorly informed consumers can protect themselves from maltreatment through sellers by asking for second opinions from other sellers. Yet, empirical evidence whether this is a successful strategy is scarce. Here we present a natural field experiment in the market for computer repairs. We find that revealing a second opinion from another expert to the seller does neither increase the rate of successful repairs nor decrease the average repair price. We assess under which conditions gathering a second opinion can be valuable.
Keywords: C93; D82; 330; Credence goods; expert services; second opinions; natural field experiment